On flexible inverse probability of treatment and intensity weighting: Informative censoring, variable selection, and weight trimming - Tompkins, Grace; Dubin, Joel A; Wallace, Michael (Statistical methods in medical research, 2025)
Many observational studies feature irregular longitudinal data, where the observation times are not common across individuals in the study. Furthermore, the observation times may be related to the longitudinal outcome. In this setting, failing to account for the informative observation process may result in biased causal estimates. This can be coupled with other sources of bias, including nonrandomized treatment assignments and informative censoring. This paper provides an overview of a flexible weighting method used to adjust for informative observation processes and nonrandomized treatment assignments. We investigate the sensitivity of the flexible weighting method to violations of the noninformative censoring assumption, examine variable selection for the observation process weighting model, known as inverse intensity weighting, and look at the impacts of weight trimming for the flexible weighting model. We show that the flexible weighting method is sensitive to violations of the noninformative censoring assumption and that a previously proposed extension fails under such violations. We also show that variables confounding the observation and outcome processes should always be included in the observation intensity model. Finally, we show scenarios where weight trimming should and should not be used, and highlight sensitivities of the flexible inverse probability of treatment and intensity weighting method to extreme weights. We conclude with an application of the methodology to a real data set to examine the impacts of household water sources on malaria diagnoses.